2016
DOI: 10.3390/molecules21030359
|View full text |Cite
|
Sign up to set email alerts
|

New Potential Pharmacological Functions of Chinese Herbal Medicines via Regulation of Autophagy

Abstract: Autophagy is a universal catabolic cellular process for quality control of cytoplasm and maintenance of cellular homeostasis upon nutrient deprivation and environmental stimulus. It involves the lysosomal degradation of cellular components such as misfolded proteins or damaged organelles. Defects in autophagy are implicated in the pathogenesis of diseases including cancers, myopathy, neurodegenerations, infections and cardiovascular diseases. In the recent decade, traditional drugs with new clinical applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 409 publications
(443 reference statements)
5
40
0
Order By: Relevance
“…PAH acts as an autophagy inducer in MFCs. Consistent with our results, several papers have shown that some natural products isolated from traditional Chinese medicine are effective to control autophagy …”
Section: Discussionsupporting
confidence: 93%
“…PAH acts as an autophagy inducer in MFCs. Consistent with our results, several papers have shown that some natural products isolated from traditional Chinese medicine are effective to control autophagy …”
Section: Discussionsupporting
confidence: 93%
“…Autophagy is a catabolic cellular process in which the dysfunctional cytoplasmic constituents are removed to maintain metabolic balance. It occurs not only in normal cells but also in cancer cells . It is widely accepted that autophagy plays a complex role in oncogenesis: it represses tumor growth in the early stages on the one hand but is required for progression to advanced or invasive tumors on the other hand .…”
Section: Discussionmentioning
confidence: 99%
“…It occurs not only in normal cells but also in cancer cells. 30 It is widely accepted that autophagy plays a complex role in oncogenesis: it represses tumor growth in the early stages on the one hand but is required for progression to advanced or invasive tumors on the other hand. 24 During the past 5 years, autophagy induced by plantderived drugs has been widely studied in various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…27) AMP activated protein kinase (AMPK) could stimulate the autophagy in skeletal muscle cells via its effect on the transcriptional function of FoxO and participate in autophagosome formation. 28) Therefore, the mTOR, AMPK, FoxO singling pathway was related to exhaustive exercise-induced skeletal muscle injury.…”
Section: Resultsmentioning
confidence: 99%